2019
DOI: 10.3390/nu11081834
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Power of the Human Milk Proteome

Abstract: Human milk is the most complete and ideal form of nutrition for the developing infant. The composition of human milk consistently changes throughout lactation to meet the changing functional needs of the infant. The human milk proteome is an essential milk component consisting of proteins, including enzymes/proteases, glycoproteins, and endogenous peptides. These compounds may contribute to the healthy development in a synergistic way by affecting growth, maturation of the immune system, from innate to adaptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 184 publications
(275 reference statements)
0
84
0
Order By: Relevance
“…By comparison to peptide sequences and their known functions, more than 300 of these peptides are considered as bioactive [ 13 ]. Until now, antimicrobial, immunomodulatory, and opioid-like functions, as well as antithrombotic and anti-hypertensive effects, have been reported for bioactive peptides [ 14 , 15 , 16 , 17 ]. Findings indicate that milk peptides can have additional physiological effects, such as antioxidant activity [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…By comparison to peptide sequences and their known functions, more than 300 of these peptides are considered as bioactive [ 13 ]. Until now, antimicrobial, immunomodulatory, and opioid-like functions, as well as antithrombotic and anti-hypertensive effects, have been reported for bioactive peptides [ 14 , 15 , 16 , 17 ]. Findings indicate that milk peptides can have additional physiological effects, such as antioxidant activity [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The composition and the level of these compounds change during the different phases of lactation in response to the changing needs of the growing and developing infant. Recent studies of the milk proteome [24] showed that between the first 72 h and 3 days postpartum the colostrum milk has the highest level of the immunoregulatory factors. The transitional milk produced between the 3rd and 15th day is very rich in proteins, and the mature, produced from day 16th, milk is enriched in fatty acids, and its overall composition becomes less variable.…”
Section: Breast Milk Immune Factorsmentioning
confidence: 99%
“…Mothers, based on their genetic status, can synthesize different sets of oligosaccharides. The most extreme interindividual differences relate to the presence or absence of fucose linked by α1,2and α1,3/4-glycosidic bonds in free oligosaccharide and glycoproteins, are conditioned by genetic factors (namely active forms of FUT2 and FUT3 genes) that affect the secretion status and Lewis blood group antigens [20,37,[55][56][57]. Two fucosyltransferases, namely FucT II (encoded by the secretory gene FUT2) and FucT III (encoded by the Lewis gene FUT3) play a key role in HMOs fucosylation.…”
Section: Structures and Diversity Of Hmosmentioning
confidence: 99%
“…It is interesting that some glycoproteins, namely IgG [68], AGP [29], and FN [31], which are present in both human milk and mother's plasma, have quite different glycosylation patterns. The changes in glycosylation are the net result of local biosynthesis of those glycoproteins by hormonally regulated alveolar cells of the mammary gland [57,69]. The fucosylation profile of the second most abundant immunoglobulin in human milk, namely IgG, was shown to differ qualitatively and quantitatively from maternal IgG [68].…”
Section: Fucosylation Of Human Milk Glycoproteinsmentioning
confidence: 99%